Madhyamaka and modern western philosophy: a report - Westerhoff, J (Equinox Publishing, 2017)
In the past the study of Asian philosophical traditions has often been approached by asking how the theories developed within these non-Western cultures would help us to solve problems in contemporary Western philosophy. The present account, which summarizes results of a research project funded by the Templeton foundation in 2015 attempts to reverse this way of studying Asian philosophy by investigating which theories, approaches and models from contemporary Western philosophy can used to support, analyze, refine and advance insights into key questions discussed by Indian Buddhist Madhyamaka. Our discussion concentrates on six key philosophical areas that can contribute in important ways to the analysis and development of Madhyamaka thought: metaphysics, logic, semantics, cognitive science, philosophy of science, and ethics.